Reconstruction of chronic scapholunate dissociation with the modified scapholunate axis method (SLAM) - Dolderer, Juergen H.; Zimny, Katja; Klein, Silvan M.; Koller, Michael; Prantl, Lukas; Geis, Sebastian (Archives of Orthopaedic and Trauma Surgery, 2019)
Introduction: Injury to the scapholunate (SL) ligament represents a common trauma of the wrist but is frequently misdiagnosed because of non-specific pain. Established methods for SL reconstruction mainly focus on reducing pain and maintaining the reposition result at the expense of mobility and strength. This study aimed at restoring stability and reducing pain while simultaneously maintaining mobility and strength using the scapholunate axis method (SLAM). Material and methods: 22 patients (19 male and 3 female) aged between 26 and 64 years with an SL ligament lesion underwent SLAM reconstruction. Mean duration between injury and operation was 7.9 ± 5 (1–24) months. Hand functions using DASH, Mayo Wrist Score, range of motion, pain (at rest and weight-bearing) and grip strength were assessed prior and 12 months postoperative. Additionally SL angle was collected pre- and postoperative. Results: Each of the 22 patients improved significantly postoperative in DASH and Mayo Wrist Score with regard to pain at rest and under weight-bearing. Additionally, grip strength could be improved up to 31% compared to preoperatively. In contrast, range of motion and SL angle and grip strength did not change essentially. Conclusions: The secondary SL ligament reconstruction technique SLAM shows promising results. Pain was significantly relieved and grip strength was significantly increased. Additionally, DASH and Mayo Wrist Score could be significantly improved. However, SL angle and range of motion could not be improved in every patient and plane.
CRIS-Team Scopus Importer:2024-12-11
Keywords: Carpal collapse; Scapholunate injury; SL dissociation; SL reconstruction; SLAC wrist